2015
DOI: 10.18632/oncotarget.3289
|View full text |Cite
|
Sign up to set email alerts
|

Variants inCDAandABCB1are predictors of capecitabine-related adverse reactions in colorectal cancer

Abstract: Adverse reactions to capecitabine-based chemotherapy limit full administration of cytotoxic agents. Likewise, genetic variations associated with capecitabine-related adverse reactions are associated with controversial results and a low predictive value. Thus, more evidence on the role of these variations is needed. We evaluated the association between nine polymorphisms in MTHFR, CDA, TYMS, ABCB1, and ENOSF1 and adverse reactions, dose reductions, treatment delays, and overall toxicity in 239 colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 38 publications
1
47
1
Order By: Relevance
“…Although fluoropyrimidines are not a known substrate of ABCB1, ABCB1 expression is induced along with 5-FU resistance in some cell lines [28], which suggests polymorphisms concerning ABCB1 activity might be related to efficacy of fluoropyrimidines. Otherwise, ABCB1 haplotype*1 was reportedly associated with capecitabine toxicity compared to variant haplotypes [29]. However, a significant relationship between ABCB1 polymorphisms and clinical outcome was not observed in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Although fluoropyrimidines are not a known substrate of ABCB1, ABCB1 expression is induced along with 5-FU resistance in some cell lines [28], which suggests polymorphisms concerning ABCB1 activity might be related to efficacy of fluoropyrimidines. Otherwise, ABCB1 haplotype*1 was reportedly associated with capecitabine toxicity compared to variant haplotypes [29]. However, a significant relationship between ABCB1 polymorphisms and clinical outcome was not observed in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, CDA was identified as a regulator of cell proliferation and chemoresistance in breast and pancreatic cancer [ 52 , 53 ]. In CRC genomic variations of CDA are associated with adverse drug response [ 63 ]. Most importantly, high expression of CDA was found in blood from CRC patients [ 64 ], hinting to a potential use of CDA as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Caronia et al genotyped 130 breast and colorectal cancer patients and found that two variants in the promoter of CDA gene rs532545 (-451 C>T) & rs3215400 (-31 del C) are in linkage disequilibrium are strongly associated with the development capecitabine induced HFS [16]. In another study conducted by Gracia [17].…”
Section: Drug Metabolizing Enzymesmentioning
confidence: 99%